Avaliação de medidas craniofaciais angulares e lineares em relação à quantidade de crescimento da face - Grossi, Ademir Tadeu Ribeiro (2005)
orthodontic diagnosis and consequent treatment plan. Thus, this research aimed to evaluate the relationships between the linear measurements N-ENA, ENA-Pog and N-Pog, the angular measurements N.OPI.ENA, ENA.OPI.Pog and N.OPI.Pog, and the VERT index according to the classification proposed by RICKETTS. The study material consisted of 700 lateral cephalograms of Brazilian leucodermic individuals of both genders (318 males and 382 females), with an average age of 16.66 years. Of the 700 radiographs, four groups were formed according to occlusion. The first group consisted of individuals with normal natural occlusion according to ANDREWS, and four of the six occlusion keys were clinically observed. The other groups consisted of individuals with Class I, II and III malocclusions according to ANGLE, without previous orthodontic treatment report. After statistical analysis for the evaluation of linear measurements N-ENA, ENA-Pog and N-Pog, and angular measurements N.OPI.ENA, ENA.OPI.Pog and N.OPI.Pog, in relation to the VERT index, showed a progressive increase of the surveyed measurements in relation to the six facial patterns determined by the VERT index, showing an increase of these measurements as it goes from the severe brachifacial pattern to the severe dolichofacial pattern. (AU)